(3eTjNI GdeQGZjs - (3LeGd GdOjf YeGQ Hf ehSi GdeQGcTj Gdecj,J (B823 (3g` s ((3CHhHcQ Hf eMeO Hf efUhQ GdcjLj s)
(3ChdgG (B:s
(3GdMeO ddg GdoeJaQO HGdYdhe hGdbOe s
(3BNQgG (B:s
(3BNQ GdLRA GdKGef hHJeGeg JeJ LejY GdeTjNI hGdMeO ddg s
(3hgh GdMGaX Rjf GdOjf CHh HcQ GdMSjf Hf YeQ GdbQTj GdYKeGfj GdeQGZj GdTGaYj bGVj WjHI GdeJhaj SfI (B816 (3g`s
(3hYdjgG NWhW HYV GdYdeGAs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JNQjL s
Keywords: (3GdJGQjNs